Patologins teologi. Om sjukdom, synd och frälsning hos Birgitta Trotzig - Bak, Krzysztof (Folia Scandinavica Posnaniensia, 2024)
This article has two aims. Firstly, it makes an attempt to shed new light on the representation of sickness in Birgitta Trotzig’s (1929–2011) writings. Secondly, the article, by using its analyses of Trotzig, tries to draw some theoretical conclusions concerning the possibilities of applying a theology of pathology in literary studies. While earlier scholars have interpreted Trotzig’s depiction of sickness by means of secular intertexts, the starting point of this article is Trotzig’s adopting of Christian anthropology as her untranscendable hermeneutic horizon. Thus, it is argued, sickness in her writings should primarily be related to theological contexts. By close reading of a representative text passage, the opening scene of Trotzig’s best known novel Dykungens dotter (The Marsh King’s Daughter, 1985), the article explores which contexts within Christian theology of sickness that would be specially fertile for an interpretation of her sickness discourse. The analyses reveal four theological notions of sickness as intertextually present in Trotzig’s narration: Augustine’s concupiscence, Sören Kierkegaard’s dispair, Pierre Teilhard de Chardin’s decomposition, and Eugen Drewermann’s neurosis. The main theoretical conclusions of the analyses are: (a) that the theological notions of sickness to a high degree differ from a ”natural” experience as well as from the biblical sources, (b) that these notions can contradict each other and generate conceptual conflicts, and (c) that the notions therefore, when applied in literary studies, demand strong hermeneutic control.